Faktor Faktor yang Mempengaruhi Produksi Ketimun di Kabupaten Hulu Sungai Tengah - Arif Hidayatullah (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2013)
This study aimed to examine the factors that influence the production of cucumber and cucumber production elasticity know Hulu Sungai Tengah Regency. The research was conducted in the Hulu Sungai Tengah. Based on the F count equal to 17.017 with a .000 Sig. From these results appear F count> F table and the Sig <alpha (0.05), then the conclusion is to reject H0, which means all of the independent variable (X) simultaneously significantly affect the dependent variable (Y). Means land, seeds, fertilizer, pesticides and labor together (simultaneously) influence the production of cucumber in Hulu Sungai Tengah Regency. The results of testing the regression coefficients are partial (t test) showed that the factors that influence the production of cucumber is a factor which is partially pesticides significantly, while the area of land, seed, fertilizer and labor is partially significant effect on the production of cucumber in the Hulu_Sungai_Tengah Regency. R Square value (coefficient of determination) is 0.739 indicates variability of production quantities of cucumber 73.9% can be explained by the factors of production are present in cucumber production function equation, while the remaining 26.1% is explained by the error factor (error). Based on the regression equation obtained, then the elasticity of production is land factor elasticity -0.013, 0.066 elasticity seeds, fertilizer elasticity is 0.799, pesticides_and_labor_elasticity_0.836,_-1.244_elasticity.